Levantine Mirage [online resource] - Malek, J; Kapitaikin, L; Choi, J; Moffett, J (University of Oxford, 2024)
Data and digitised images of 19th-century "studio photographs" of the Levant, mainly in the collection of the Griffith Institute, Oxford. The original online resource was published by the Griffith Institute in 2005; a new version was published in 2023 on the Sustainable Digital Scholarship platform.